Which body comes first? (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article juxtaposes fragments from three Brazilian plays premiered in the last decade by artists who engage with debates on gender identities to explore the effects of discourses on their bodies: Manifesto Transpofágico by Renata Carvalho, E.L.A. by Jéssica Teixeira, and Vaga Carne by Grace Passô. Given the various operations through which a speaking being relates with its body, modes of entrapment, and its remnants, the article proposes twists that critically and poetically question these entanglements, based on psychoanalytic propositions about the speaking body derived from Jacques Lacan's later teachings.
Keywords: body; discourse; language; psychoanalysis; theatre